Japanese surgical resource utilization in 2016. Issue 6 (8th July 2019) - Nakata, Yoshinori; Watanabe, Yuichi; Narimatsu, Hiroto; Yoshimura, Tatsuya; Otake, Hiroshi; Sawa, Tomohiro
Abstract : Purpose: The purpose of this paper is to examine from the viewpoint of resource utilization the Japanese surgical payment system which was revised in April 2016. Design/methodology/approach: The authors collected data from surgical records in the Teikyo University electronic medical record system from April 1 till September 30, 2016. The authors defined the decision-making unit as a surgeon with the highest academic rank in the surgery. Inputs were defined as the number of medical doctors who assisted surgery, and the time of operation from skin incision to closure. An output was defined as the surgical fee. The authors calculated each surgeon's efficiency score using output-oriented Charnes–Cooper–Rhodes model of data envelopment analysis. The authors compared the efficiency scores of each surgical specialty using the Kruskal–Wallis and the Steel method. Findings: The authors analyzed 2, 558 surgical procedures performed by 109 surgeons. The difference in efficiency scores was significant ( p = 0.000). The efficiency score of neurosurgery was significantly greater than obstetrics and gynecology, general surgery, orthopedics, emergency surgery, urology, otolaryngology and plastic surgery ( p <0.05). Originality/value: The authors demonstrated that the surgeons' efficiency was significantly different among their specialties. This suggests that the Japanese surgical reimbursement scales fail to reflect resource utilization despite the revision in 2016.